Immunomodulatory streptococci that inhibit CXCL8 secretion and NFκB activation are common members of the oral microbiota. Issue 3 (18th March 2021) - Myers, Sarah; Do, Thuy; Meade, Josephine L.; Tugnait, Aradhna; Vernon, Jon J.; Pistolic, Jelena; Hancock, Robert E. W.; Marsh, Philip D.; Trivedi, Harsh M.; Chen, Dandan; Devine, Deirdre A.
Abstract : Introduction. Oral tissues are generally homeostatic despite exposure to many potential inflammatory agents including the resident microbiota. This requires the balancing of inflammation by regulatory mechanisms and/or anti-inflammatory commensal bacteria. Thus, the levels of anti-inflammatory commensal bacteria in resident populations may be critical in maintaining this homeostatic balance. Hypothesis/Gap Statement. The incidence of immunosuppressive streptococci in the oral cavity is not well established. Determining the proportion of these organisms and the mechanisms involved may help to understand host-microbe homeostasis and inform development of probiotics or prebiotics in the maintenance of oral health. Aim. To determine the incidence and potential modes of action of immunosuppressive capacity in resident oral streptococci. Methodology. Supragingival plaque was collected from five healthy participants and supragingival and subgingival plaque from five with gingivitis. Twenty streptococci from each sample were co-cultured with epithelial cells±flagellin or LL-37. CXCL8 secretion was detected by ELISA, induction of cytotoxicity in human epithelial cells by lactate dehydrogenase release and NFκB-activation using a reporter cell line. Bacterial identification was achieved through partial 16S rRNA gene sequencing and next-generation sequencing. Results. CXCL8 secretion was inhibited by 94/300 isolates. Immunosuppressive isolates were detected in supragingival plaque from healthy (4/5) and gingivitis (4/5) samples, and in 2/5 subgingival (gingivitis) plaque samples. Most were Streptococcus mitis/oralis . Seventeen representative immunosuppressive isolates all inhibited NFκB activation. The immunosuppressive mechanism was strain specific, often mediated by ultra-violet light-labile factors, whilst bacterial viability was essential in certain species. Conclusion. Many streptococci isolated from plaque suppressed epithelial cell CXCL8 secretion, via inhibition of NFκB. This phenomenon may play an important role in oral host-microbe homeostasis.